Hubungan Antara Kontrol Diri dengan Gaya Hidup Hedonis pada Mahasiswa Universitas Negeri Padang - Khairu Nisa Afifah; Mario Pratama (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
A hedonic lifestyle is a lifestyle in which individuals spend time and money that serves only as motivation, a social class with conceptions that reflect the individual who uses it. The study aims to describe the relationship between self-control and hedonistic lifestyles in students at Padang State University. This research uses a quantitative approach. The population in this study consisted of students at State University Padang with a total sample of 119 students using purposive techniques. The data collection using a scale with a hedonist lifestyle measurement tool organized by Amelia Acmel (2022) refers to the hedonistic lifestyle aspects proposed by Engel et al (1994), and the self-control measuring tool developed by Anggraeni (2022), referred to Averril (1973)'s self-controllment aspects as the instruments used in this research. Data analysis in this study uses product moment correlation techniques. The results of the analysis showed that there was a negative relationship between self-control and hedonistic lifestyles in students at Padang State University with statistical results of correlation coefficients r = -0,379 and p = 0,000 (p<0,5).